The quality of reporting of randomized controlled trials of HuatuoZaizao pill for stroke - Zhang, Xiao-Jie; Wang, Yi-Jing; Lu, Xiao; Ying, Peng-Jie; Qian, Shi-Yan; Liang, Jie; Zheng, Guo-Qing (Frontiers in Pharmacology, 2023)
Background: HuatuoZaizao pill (HZP), a Chinese patent medicine, is often used in the treatment of stroke. However, there is still a lack of enough evidence to recommend the routine use of HZP for stroke. This study is aimed at evaluating the quality of reporting of randomized controlled trials (RCTs) on HZP for stroke. Methods: RCTs on HuatuoZaizao pill for stroke were evaluated by using Consolidated Standards of Reporting Trials (CONSORT) guidelines and CONSORT extension criteria on reporting herbal interventions (CONSORT-CHM) guidelines. Microsoft Excel 2007 and SPSS20.0 was used for statistics analyses. Results: Seventeen studies involving 1801 stroke patients were identified. CONSORT-CHM has expanded 24.3% (9/37) items in CONSORT and added a small item. The average scores of CONSORT evaluation is 14.6, while the average scores of the CONSORT-CHM evaluation is 11.6. The central items in CONSORT as eligibility criterion, sample size calculation, primary outcome, method of randomization sequence generation, allocation concealment, implementation of randomization, description of blinding, and detailed statistical methods were reported in 77%, 6%, 100%, 47%, 6%, 6%, 6%, and 94% of trials, respectively. In terms of the CONSORT-CHM, none of the articles reported in detail the dosage form, origin, formula basis and so on of HZP, and only half of studies reported the outcome indicators related to Traditional Chinese Medicine syndromes. Conclusion: The overall report quality of RCT related to HZP is low. HZP still needs to report higher quality RCTs to prove its effectiveness and safety.